2010
DOI: 10.1021/jp908931w
|View full text |Cite
|
Sign up to set email alerts
|

Effect of N-Substituents on Redox, Optical, and Electronic Properties of Naphthalene Bisimides Used for Field-Effect Transistors Fabrication

Abstract: Three groups of naphthalene bisimides were synthesized and comparatively studied, namely, alkyl bisimides, alkylaryl ones, and novel bisimides containing the alkylthienyl moiety in the N-substituent. The experimental absorption spectra measured in CHCl(3) exhibit one intensive absorption band that is uniformly detected in the spectral range of 340 to 400 nm for all studied molecules. This band consists of three or four vibronic peaks. The introduction of an alkylthienyl group results in the appearance of an ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 41 publications
4
40
0
Order By: Relevance
“…A short inspection of the results indicates that HOMO and LUMO values fall quite low in the energy scale indicative of the facilitated electron injection process in the compounds under consideration. [ 26 ] LUMO energies of ND1−ND3 are close and comparable, while the LUMO of ND4 is positioned much lower (−3.78 eV) due to the presence of 1,3,4-thiadiazolyl moiety, which is characterized by higher accepting strength than pyridinyl fragments. Apparently, asymmetrical compounds exhibit similar LUMO energies with slightly lower ones found for ND6 , ND8 , and ND10 , bearing pyrimidinyl unit in the condensed part.…”
Section: Theoretical Calculationsmentioning
confidence: 99%
“…A short inspection of the results indicates that HOMO and LUMO values fall quite low in the energy scale indicative of the facilitated electron injection process in the compounds under consideration. [ 26 ] LUMO energies of ND1−ND3 are close and comparable, while the LUMO of ND4 is positioned much lower (−3.78 eV) due to the presence of 1,3,4-thiadiazolyl moiety, which is characterized by higher accepting strength than pyridinyl fragments. Apparently, asymmetrical compounds exhibit similar LUMO energies with slightly lower ones found for ND6 , ND8 , and ND10 , bearing pyrimidinyl unit in the condensed part.…”
Section: Theoretical Calculationsmentioning
confidence: 99%
“…The growth of modern technology has posed a constantly increasing need for materials that can perform well under harsh conditions, such as elevated temperatures, 4 and processable PIs with special properties have become a subject of great interest all over the world. 5,6 It was found that compounds containing imine rings have prospective applications in organic (opto)electronics and related fields, and that they are exemplary as materials for fabricating field-effect transistors, [6][7][8] organic light-emitting diodes, 9-12 solar cells [12][13][14] and photonic devices. [15][16][17] With regard to the PI microstructure, much effort is being devoted to the design and synthesis of PIs with thioether linkages.…”
Section: Introductionmentioning
confidence: 99%
“…[23] In the case of NBI-(DTP) 2 the value of E red1-E red2 is by 0.05 to 0.08 Vl ower than in naphthaleneb isimides that are not core-functionalized. [19,22] This may suggest that the radical anion charged ensity is partially delocalized from the core to dithienopyrrole substituents, as corroboratedb yt he DFT calculations of unpaired spin density distribution (vide infra). The electrochemical data, concerning the negative potentialr ange, are collected in Table 1.…”
Section: Cyclic Voltammetry and Epr Spectroelectrochemistry Versus Dfmentioning
confidence: 69%
“…UV/Vis spectra of naphthalene bisimides with no substituents in the core are characterized by as trong absorption band of av ibronic character,a scribed to the arylene p-p*t ransition, with the 0-0 vibronic peak, in the vicinity of 380 nm, showing the highesti ntensity. [19] Core functionalization of these compounds with electron-donatings ubstituents gives rise to an ew band at significantly longerw avelengths, usually of charge-transfer (CT) character. [6b, 20] This CT band, with am aximum at 689 nm, is also clearly seen in the spectrum of NBI-(DTP) 2 (Figure 1a).…”
Section: Opticalproperties:e Xperimental Versus Dft Calculationsmentioning
confidence: 99%